(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Diabetes mellitus is a metabolic disorder affecting every age group worldwide. Sedentary lifestyle, obesity and lack of physical activity are the main causes of type 2 diabetes. Hyperglycemia is not controlled; it may result in macrovascular and microvascular complications which are the major causes of morbidity and mortality in diabetic patients. Doing exercise regularly and consumption of low-calorie diet can help diabetic patients in keeping blood glucose levels under control. Present case study was a 67-year-old woman who was diagnosed with type 2 diabetes. Her anthropometric measurements were recorded as height was 152 cm, weight was 70.75 kg and BMI was 30.4 kg/m2. Her biochemical parameters are HDL is 38, triglycerides are 163, and cholesterol is 184, VLDL is 33, FBS is 115mg/dl, PLBS is 250mg/dl and HbA1c is 9.5mg/dl. She was supplemented with 10gm of Tennetti-tilla (dried fig and sesame seed laddu) daily for 90 days. After the period of intervention of 90 days, the changes observed as reduction in weight to 68kg, FBS 87mg/dl, PLBS 106, cholesterol is 188, triglycerides are 71, HDL is 45, and HbA1c is 6.3 and VLDL is 14.2mg/dl. The study reveals that supplementation of 10g of Tennetti-tilla (dried fig and sesame seed laddu) for 90 days can reduce hyperglycemia in type 2 diabetic patients.